ChemInform Abstract: Unsymmetrical Tetrasubstituted Ureas from Tertiary Carbamoylimidazole: Activation by AlMe3. Issue 2 (9th January 2013) - Velavan, A.; Sumathi, S.; Balasubramanian, K. K.
Abstract A general and efficient access towards unsymmetrical urea derivatives is presented, involving the amination of carbamoylimidazoles in the presence of AlMe3.